Calvyn oor God se gebruik van middele in sy voorsieningshandelinge - P. C. Potgieter (Acta Theologica)
Obviously not enough research has been done regarding Calvin’s view on the use of media by God in his acts of providence. Read superficially, some passages in his writings suggest that he may even regard the eternal Word and the Spirit of God as media of providence. The context however clearly indicates that this is not the case. But then again the question arises whether he does not see particular attributes of the Word and the Spirit as media of providence. This, however, poses the problem that God’s attributes are essential to his being, and thus cannot function as external media. His very frequent use of the Latin term arcanus in conjunction with media of providence suggests that in essence the providential acts of God remain a mystery for us, unless it is — in some instances — revealed to us in his Word.